(untitled) (Research, Society and Development, 2022)
The article aims to present itself as research and discussions about gamification in Higher Education of Accounting Sciences, in the last five years, in the areas of Education and Applied Social Sciences. This is a systematic review with a search in the Catalogue of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), using the descriptor the descriptor "Gamification". When the inclusion and exclusion criteria were applied, 132 studies were found that were analysed from the Content Analysis (CA) of Bardin (2011). In the mapping performed, there was no research with gamification in the Teaching of Accounting. However, five categories of analysis were constructed, deprecating the insertion of Gamification in Basic Education, Technological Professional Education, Teacher Training and Corporate Education. As research esthesing as a tendency to analyse the use of gamification as a strategy in the teaching and learning process in the perspective of increasing the participation of students in classes.